Towards sustainable arts : European best practices and policies - Knol, Jan Jaap; Pigaht, Janina; Schrijen, Bjorn (Boekman Foundation, 2022)
In 2021, forest fires, drought and floods communicated one clear and disquieting message: time is running out, the future is now. That future needs to be green and sustainable, requiring a massive societal transformation. Arts and culture can play an important role in this necessary transition. The new publication 'Towards sustainable arts: European best practices and policies' explores how this role takes shape in seven European countries, and offers inspiring examples and best practices for artists, cultural organisations and policy makers. In seven chapters, experts from the Czech Republic, Finland, Flanders, Germany, the Netherlands, Scotland and Spain investigate how cultural organisations in their country are becoming more sustainable, how artists are engaging with the climate crisis, and which role culture has in the general transition towards a greener society. While each chapter contains many inspiring initiatives and ideas unique to each country, there are also striking similarities. In most countries sustainability is lacking in national cultural policy, and culture is missing in climate policy. There is however a need for sustainable cultural policy: among other things to counter fragmentation of initiatives, to enhance collaboration or to offer funding, support and financial security. Another significant observation underlying all contributions is the importance of collaboration and of networks, which have achieved great results in the countries included in the publication. The publication Towards sustainable arts was initiated by the Boekman Foundation, with chapters contributed by experts from the Czech Republic, Finland, Flanders, Germany, the Netherlands, Scotland and Spain whose work or research concerns the topic of culture and sustainability. We would like to express our deepest thanks and appreciation to all the authors for their work and contribution: Pavla Petrová (Czech Republic / Arts and Theatre Institute), Maria Hirvi-Ijäs, Anna Kanerva, Marjo Mäenpää (Finland / Cupore), Nikol Wellens (Flanders / Kunstenpunt), Marje Brütt (Germany / Kulturpolitische Gesellschaft), Sofie Krop, Mareile Zuber (The Netherlands / Het Groene Cultuur Bureau), Ben Twist, Katherine Denney (Scotland / Creative Carbon Scotland), Jordi Baltà Portolés and Herman Bashiron Mendolicchio (Spain / Trànsit Projectes and University of Barcelona).
Keywords: taide; taideala; kestävä kehitys; kulttuuri; kulttuuripolitiikka; ilmastonmuutokset; ilmastopolitiikka; Eurooppa